Electric Field Analysis Along Pin-Plane Electrodes In Sir Containing - Zakariah, Muhammad Saiful (Universiti Sains Malaysia, 2017)
Silicon Rubber is a polymer insulator that is widely used in high voltage application due to its good electrical insulating properties and can withstand high temperature. Polymer insulators were found having degradation phenomena after long time usage and lead to breakdown. Electrical treeing is found as one of the causes of the cable breakdown. Nanofiller is found effective in inhibiting the electrical treeing growth during experiment setup. However, the electric field distribution in electrical treeing are still not well known. In this project, the simulation model of electrical treeing setup is developed and successfully executed. The electric field distribution containing various concentrations of nano-alumina in insulating materials is investigated using pin-plane electrodes model by using Finite Element Method (FEM) software, Comsol Multiphysics. As a result, the electric field intensity drops within the nanofiller. The electric field intensity at interface is increasing when concentration of nano-alumina increases due to changes in interparticle distance. Lastly, the output of this project can be compared with the experimental setup done by previous works. This project will give understandings about the electric field distribution in electrical treeing.